An improved WOA of PI control for three phase PWM rectifier - G, Shwetha; K P, Guruswamy (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
In the empire of electric vehicle (EV) propulsion systems, efficient energy conversion is paramount for extending driving range and enhancing overall performance. Rectifiers play a crucial role in converting AC from the grid into DC for battery charging and motor operation. However, the performance of rectifiers is heavily influenced by the control algorithms employed. This work presents an optimized proportional-integral (PI) controller design for rectifiers in EV applications. The proposed controller aims to achieve high efficiency, fast response, and robustness to variations in load and input voltage. The optimization process incorporated in this work utilized whale optimization topology for tuning the PI controller parameters. The objective is to minimize cost function that represents deviation of rectifier output from desired characteristics under various operating conditions. The outcomes of simulation demonstrate that suggested controller works to provide greater accuracy than traditional control techniques. Moreover, experimental validation verifies the proposed controller's reliability and efficiency in practical EV applications. The optimized PI controller contributes to maximizing energy efficiency, extending battery life, and enhancing the overall reliability of electric vehicle propulsion systems.